El Excentrico, 1969-12-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
December 20, 1969 [20 de diciembre de 1969]. No volume or issue number. Cover has a Christmas Greeting Card with photo of Lena Manriquez Gomez who was advetising for an Income Tax Service.